Intermediate Excel 2010 - Conway, Pamela; Safari eBooks ([S.l.] : CompuWorks, 2012)
"In this course you will learn how to use multiple worksheets and workbooks efficiently. You will also learn how to create outlines and subtotals, how to create and apply cell names, and how to create and format charts. You will work with templates, collaborate in workbooks and use the drawing tools to enhance and annotate spreadsheets."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 8, 2013).
Presenter, Pamela Conway.
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets; Business -- Computer programs; Electronic books